Poor Performance of Hepatitis C Antibody Tests in Hospital Patients in Uganda - Seremba, E.; Ocama, P.; Opio, C.K.; Kagimu, M.; Thomas, D.L.; Yuan, H.J.; Attar, N.; Lee, W.M. (Journal of medical virology, 2010)
Most hepatitis C testing in Uganda is performed using commercial rapid strip assays (RSA) to detect antibodies to hepatitis C virus (anti-HCV), rather than enzyme immunoassays (EIA). The prevalence of hepatitis C antibodies in a Ugandan hospital population was determined using both methods to test their accuracy using nucleic acid testing (NAT) as a reference. Sera from 380 consecutive hospitalized Ugandan patients were tested for anti-HCV using anRSAin Uganda, with subsequent automated third-generation EIA testing in the United States, followed by NAT. Recombinant immunoblot assays (RIBA) were used as a supplementary test to detect anti- HCV epitopes. Overall, anti-HCV was detected in 48/380 (13%) by one or both antibody tests. Anti-HCV was detected in 19 (5.0%) patients by RSA and in 33 (8.7%) patients by EIA; only four patients were anti-HCV positive by both methods. Fourteen of the 48 anti-HCV positive patients had detectable serum HCV RNA, 7 each by bDNA assay or by PCR. RSA detected only 7 of 14 HCV RNA positive sera. Of 29 RNA negative but anti-HCV positive patients tested by RIBA, only two were anti-HCV positive; 27 were anti-HCV negative or indeterminate. Anti-HCV testing by RSA and/or EIA was neither sensitive nor specific for detection of ongoing HCV infection in hospitalized Ugandan patients. Our findings underscore the importance of confirmatory nucleic acid testing, which, despite its increased cost, appears essential to manage African patients with HCV.
Keywords: Rapid slide test; Enzyme immunoassay; Nucleic acid testing; Anti-HCV